Vida e cotidiano dos pescadores artesanais de nossa senhora do livramento, santa rita, pb: aspectos gerais e etnoconhecimento - Sousa, Maria Glória de (2010)
The present research is guided by the relevance of the redefinition process of the traditional knowledge of fishermen craftsmanship in the district of Nossa Senhora do Livramento in Santa Rita, Paraiba, in relation to the working techniques used by fishermen in the estuarine/mangrove area, focusing on the existing relationship of man with the environment from which "local geographic knowledge" has been derived over the years. We have attempted to characterize the different aspects of local knowledge, seeking to understand how that knowledge was acquired and how it was transmitted from generation to generation. We have also sought to assess the implications of the extractive practices adopted on fisheries resources by identifying and mapping the fishing areas used by local fishermen. Qualitative and quantitative methods have been used (Northeastern, 1992); (NISHIDA, 2000); (ALVES & NISHIDA, 2003). The sampling universe was defined by means of the snowball technique [snowball] (BAILEY, 1982). Aiming at making the search more grounded, we have interviewed a diverse audience, encompassing all age groups, ranging from10 to 60 years of age and over. The expansion of the sampling was done according to the indication of those being interviewed, that is, each individual interviewed suggested another individual, which shows a considerable consistency as to the consistence of the information obtained, revealing, therefore, considerable support to secure the size and importance of the sample. This methodological approach is based on Alexiades (1999). In total, we interviewed 70 residents of the community of Nossa Senhora do Livramento: 40 related to the study of the socioeconomic profile of the community, and 30 related specifically to fishing activities. It was also used the technique of guided tours in the countryside, where fishermen and shellfish collectors indicated areas to be covered during the fishing activities (GRENIER, 1998). The data obtained in the field were analyzed based on qualitative and quantitative techniques. Qualitatively, these data were analyzed using an emicist/ethicist approach. The results showed how estuaries and wetlands associated with them are of enormous importance to the community under study. The study has also demonstrated the value of traditional knowledge or "ethno-knowledge", which must be protected as a way of preserving their identity.